Identity, Power, and Prestige in Switzerland's Multilingual Education - Becker, Anna (Pädagogik, 2023)
Switzerland is known for its multilingualism, yet not all languages are represented equally in society. The situation is exacerbated by the influx of heritage languages and English through migration and globalization processes which challenge the traditional education system. This study is the first to investigate how schools in Grisons, Fribourg, and Zurich negotiate neoliberal forces leading to a growing necessity of English, a romanticized view on national languages, and the social justice perspective of institutionalizing heritage languages. It uncovers power and legitimacy issues and showcases students' and teachers' complex identities to advocate equitable multilingual education.